Human Papillomavirus Infectious Entry and Trafficking Is a Rapid Process - Broniarczyk, Justyna (J Virol, 2015)
Previous studies have indicated that human papillomavirus (HPV) infectious entry is slow, requiring many hours after initial infection for the virus to gain entry into the nucleus. However, intracellular transport pathways typically are very rapid, and in the context of a natural HPV infection in a wounded epithelium, such slow intracellular transport would seem to be at odds with a normal viral infection. Using synchronized cell populations, we show that HPV trafficking can be a rapid process. In cells that are infected in the late S-early G(2)/M phase of the cell cycle, HPV16 pseudovirion (PsV) reporter DNA gene expression is detectable by 8 h postinfection. Likewise, reporter DNA can be visualized within the nucleus in conjunction with PML nuclear bodies 1 h to 2 h postinfection in cells that are infected with PsVs just prior to mitotic entry. This demonstrates that endosomal trafficking of HPV is rapid, with mitosis being the main restriction on nuclear entry. IMPORTANCE HPV infectious entry appears to be slow and requires mitosis to occur before the incoming viral DNA can access the nucleus. In this study, we show that HPV trafficking in the cell actually is very rapid. This demonstrates that in the context of a normal virus infection, the cell cycle state will have a major influence on the time it takes for an incoming virus to enter the nucleus and initiate viral gene expression.